Identoralities in Mia Couto - Ribeiro, Orquídea; Moreira, Fernando (Revista de Letras, 2020)
Mia Couto states that “African culture is not a single one but a multicultural network in continuous construction” (COUTO, 2005, p. 79). The idea of a multiple and plural identity is related to the questions of tradition and roots of a people, with the need to “re-construct” rituals and beliefs, fundamental elements for the reconstruction of the identity of a country marked by war. The sixteen-year war with the desolation of the natural and human landscape did not provide a cultural context suitable for oral transmission. The need to rescue “the ancestral Mozambican imagery deeply rooted in orality (MARTINS, 2002), lost or forgotten, remains up-to-date and linked to the question of the definition of identity, of Mozambican cultural identity. Oral tradition helps to recycle and revive the collective memory and traditional culture of the Mozambican people, but orality alone is not enough to combat forgetfulness; it is necessary to write to reinforce and diversify the process of re-creating this tradition. Mia Couto contributes to the recovery of tradition with his stories, creating a space “between places”, in which elements of modernity, through the bias of prosaic-fictional writing, are used to transform, update and invigorate the traditional cultural heritage and thus renew the process of building the collective identity of Mozambique. Through readings of Mia Couto’s short narratives and novels, the intention is to explore how the author uses orality to re-construct the identity of the characters and consequent revitalization of collective cultural memory, analyzing selected texts in which identity and orality merged to portray the Mozambican identity. Reinventing or hearing forgotten voices is coloring and building the new Mozambican cultural identity, giving the anonymous people an opportunity to express themselves, to identify with and to give a life to a cultural project for a future that is always under construction.